A jeśli nie religia, to co jest ważne? Zróżnicowanie wewnątrz i międzypokoleniowe systemów aksjonormatywnych młodych Polaków - Bożewicz, Marta (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2025)
The crises of recent years, including the pandemic, the war in Ukraine, and economic instability, may disrupt the mechanism described by Inglehart, according to which increasing existential security in a society leads to the adoption of post-materialist values. The aim of the article is to identify the value hierarchy of young Poles, with particular attention to the place of religious faith, and to show intergenerational (Generations Y and Z) as well as intragenerational differences. The empirical data analyzed come from quantitative research conducted by CBOS, primarily from a representative survey of individuals aged 18–44 carried out in November 2024. Student’s t-tests were used to compare means, along with an analysis of response distributions. For trend data from 2017–2025, indicators of declared faith and religious practices were examined. Differences between Generations Y and Z are minor, while differences between women and men are clearly pronounced: women rate the importance of values such as equal treatment of others, education, engagement with culture, respect from other people, and ecology, environmental care significantly higher. The downward trend in religious practice in Poland slowed after the pandemic, and 2025 saw an increase in declared religiosity among young people. The accumulation of crises shifts young cohorts toward security-related values, indicating a weakening of the post-materialist dynamic expected under Inglehart’s theory. At the same time, strong intragenerational differences between women and men suggest that these gender differences – rather than generational divisions per se – may become a key factor in explaining contemporary value orientations among young Poles.